2009
DOI: 10.1007/s11605-008-0595-7
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Cocoon: Clinical Presentation, Diagnosis, and Management

Abstract: A 15-year-old girl presented with features suggestive of sub-acute intestinal obstruction (SAIO) with a palpable abdominal lump. Contrast-enhanced computed tomogram (CECT) abdomen revealed congregated small gut loops confined to a single area and encased in a thick membrane suggestive of abdominal cocoon. On laparotomy, a thick white membrane was found encasing most of the small gut. The cocoon was excised releasing the encased small bowel. The patient was relieved of her symptoms following surgery. Histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 5 publications
1
19
1
7
Order By: Relevance
“…Currently accepted is that the abdominal CT scan can provide more accurate information on the diagnosis of abdominal cocoon and sometimes the degree of obstruction and the types of bowel loops involved. 3 It has been demonstrated that, on the CT scans, a conglomerate of several small-bowel loops (both jejunal and ileal) was seen in the centre of the abdomen, a thick enhancing membrane surrounded the bowel, forming a saclike structure or a cocoon; mild fluid was seen between these encapsulated bowel loops, some of which were closely apposed and probably adhered to each other. 4 Other features include mural thickening of intestinal loops, peritoneal thickening with enhancement, peritoneal or mural calcifications, and reactive adenopathy, described in another literature, were also found to be statistically correlated with the appearance of abdominal cocoon.…”
Section: Discussionmentioning
confidence: 99%
“…Currently accepted is that the abdominal CT scan can provide more accurate information on the diagnosis of abdominal cocoon and sometimes the degree of obstruction and the types of bowel loops involved. 3 It has been demonstrated that, on the CT scans, a conglomerate of several small-bowel loops (both jejunal and ileal) was seen in the centre of the abdomen, a thick enhancing membrane surrounded the bowel, forming a saclike structure or a cocoon; mild fluid was seen between these encapsulated bowel loops, some of which were closely apposed and probably adhered to each other. 4 Other features include mural thickening of intestinal loops, peritoneal thickening with enhancement, peritoneal or mural calcifications, and reactive adenopathy, described in another literature, were also found to be statistically correlated with the appearance of abdominal cocoon.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a thick fibrotic membrane that encases the bowel, forming a sac or cocoon along with some internal adhesions. At times, the surrounding membrane may be thin and difficult to identify on a CT scan (3,4,8).…”
Section: Discussionmentioning
confidence: 99%
“…Membranın oluşumunu açıklayan farklı hipotezler mevcuttur fakat bu hipotezleri destekleyen objektif bir kanıt henüz yoktur. Hastanın bariz abdominal bulguları yokken tekrarlayan düşük seviyeli veya subklinik peritonit ve sonrasında onun neden olduğu skleroz ve membran oluşumu ve sonunda koza oluşumu, abdominal kozanın patogenezi için en akla yatkın olan hipotezdir 8 .…”
Section: Tartıșmaunclassified